Manufacture of scaffolds for cell cultures: automation of supply modules - Carvajal-Araya, Jorge (2020)
A manufacturing system for cellular culture scaffolds is under development. The system requires to create very thin fibers that are in the scale of nanometers using a process called electrospinning. This article presents the implementation of the mo